Synthesis of AFe2O4 (A=Fe, Mn, Co) nanoparticles for the magnetic hyperthermia treatment of Cancer - Chandel, Abhishek (My University, 2022)
With 10 million deaths in 2020 cancer remains one of the most challenging diseases in contemporary medicine. Chemotherapy, surgery, and radiation therapy severely harm healthy tissues and succeed rarely in advance stages of cancer. Recent studies indicate that magnetic hyperthermia, which involves targeted delivery of magnetic nanoparticles to tumor cells followed by localized remote heating of cancer tissues could revolutionize clinical practice in the treatment of cancer, either as standalone intervention or adjunct to radiotherapy or chemotherapy. Water dispersible magnetic nanoparticles (MNPs) of ferrites (AFe2O4; A=Fe, Mn, Co) are the promising candidates for magnetic hyperthermia due to their high chemical stability, biocompatibility, moderate magnetization and high specific absorption rate (SAR). In this thesis, magnetic hyperthermia efficiency of water based magnetic fluids of AFe2O4 (A=Fe, Mn, Co) nanoparticles is evaluated. AFe2O4 (A=Fe, Mn, Co) nanoparticles were synthesized by chemical co-precipitation method. Nanoparticles were coated with a bilayer of oleic acid and dispersed in water. Nanoparticle concentrations in magnetic fluids were 70 mg/mL for Fe3O4, 200 mg/mL for MnFe2O4 and 60 mg/mL for CoFe2O4. Structural and magnetic properties of MNPs were investigated by X-Ray diffraction (XRD) and vibrating sample magnetometer (VSM), respectively. XRD study revealed that AFe2O4 nanoparticles (NPs) exhibits cubic inverse spinel structure. Synthesized nanoparticles are soft ferromagnetic with very narrow hysteresis loops. Magnetic hyperthermia study was carried out as a function of magnetic field strength (2-10 mT) and field frequency (162-935.6 kHz) for 10 minutes. MNPs exhibits highest SAR values for 10 mT field strength at 935.6 kHz. Amongst the tested MNPs, Fe3O4 possess the highest SAR value (27.35 W/g), followed by MnFe2O4 (1.91 W/g) and CoFe2O4 (0.94 W/g). Considering this, it is concluded that amongst the studied inverse spinel ferrite nanostructures AFe2O4 (A=Fe, Mn, Co), Fe3O4 nanoparticles are most suitable for magnetic hyperthermia applications.
Keywords: Magnetic nanoparticles; Hyperthermia; Coprecipitation; Ferrites; Cancer